PENGARUH E-REKRUTMEN DAN REPUTASI PERUSAHAAN TERHADAP MINAT KERJA MAHASISWA UNIVERSITAS BUANA PERJUANGAN KARAWANG - Widia, Elta; Isyanto, Puji (Jurnal Manajemen dan Bisnis, 2025)
This study aims to examine the influence of e-recruitment and corporate reputation on the job interest of students at Buana Perjuangan University Karawang. The research method used is quantitative with a survey approach. The sample consists of 100 respondents, who are Management students from the 2022 batch at Buana Perjuangan University Karawang, selected using purposive sampling. Data collection was conducted through online questionnaires. The collected data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results show that both e-recruitment and corporate reputation significantly affect students’ job interest. E-recruitment has a positive effect, indicating that an effective digital recruitment system increases students' interest. In contrast, corporate reputation has a negative effect, suggesting that a poor perception of the company can reduce job application interest. Together, these two variables explain 32.9% of the variance in students’ job interest.